PEDULI KEBERSIHAN LINGKUNGAN MELALUI PROGRAM BAKTI SOSIAL MAHASISWA BARU DAN SIVITAS AKADEMIKA UNIVERSITAS SAMAWA DI TAMAN MANGGA - Asmini Asmini; Novi Kadewi Sumbawati; Ismawati Ismawati; Rosyidah Rachman (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Environmental cleanliness is something that is very urgent for the community, especially the people of Sumbawa district, especially in the midst of the current covid pandemic condition, one of the efforts to prevent the transmission of covid 19 and also several other diseases, then one of the solutions carried out is environmental hygiene activities with community service, namely activities to care for environmental cleanliness through social service programs for new students and the academic community of Samawa University. The purpose of this community service activity is to help overcome environmental hygiene problems in the community, especially in the Sumbawa Regent's office, to train students, especially new students, to have an attitude of caring for the environment, and to realize the Tri Dharma of Higher Education. This activity is a Community Service Activity carried out by new students for the 2021/2022 academic year and the Samawa University academic community from the highest ranks consisting of Chairman of the Foundation's Board of Trustees, Chancellors, Vice-Chancellors, Deans, Head of Study Programs, Lecturers and Staff as well as participating also supported by the presence of Mr. Regent and Mrs. Deputy Regent of Sumbawa Besar. This activity was carried out in the office of the Regent of Sumbawa Besar. with the method of social service. And this environmental cleaning activity begins with the preparation of gathering new students and the Samawa University academic community. The next step is to go to the Sumbawa Regent's office and do a social service by cleaning the mango garden area by collecting and disposing of garbage. After the activity is complete, the participants return to their respective addresses. The New Student Social and the Samawa University Academic Community is running well and smoothly and has full support from the Sumbawa Regency Government and with this community service, it is hoped that the community will have the motivation to keep the environment clean.